The occurrence of dauciform roots amongst Western Australian reeds, rushes and sedges, and the impact of phosphorus supply on dauciform-root development in Schoenus unispiculatus (Cyperaceae) - Shane, Michael W (The New phytologist, 2005)
* The incidence of species that develop specialised 'dauciform' lateral roots, which are hypothesised to be important for phosphorus (P) acquisition, is uncertain. We investigated their occurrence in Australian reed, rush and sedge species, grown at low P concentration in nutrient solution, and studied the response of Schoenus unispiculatus (Cyperaceae) to a range of P concentrations. * We assessed the fraction of root biomass invested in dauciform roots, their respiration and net P-uptake rate, and the P status of roots and leaves. * Dauciform-root development occurred only in particular genera of Cyperaceae when grown at low P supply. Increased P supply was associated with increased growth of S. unispiculatus and increased leaf [P]. Dauciform-root growth was reduced by increased P supply, and reduced P uptake co-occurred with the complete suppression of dauciform roots. * The P-induced suppression of dauciform roots in Cyperaceae is similar to that observed for proteoid roots in members of Proteaceae and Lupinus albus. The response of dauciform roots to altered P supply and their absence from root systems of some sedge species are discussed in terms of managed and natural systems